1993
DOI: 10.1111/j.1365-2125.1993.tb05695.x
|View full text |Cite
|
Sign up to set email alerts
|

A placebo controlled double‐blind evaluation of the pharmacodynamics of fengabine vs amitriptyline following single and multiple doses in elderly volunteers.

Abstract: GU7 lUF and 2Synthelabo Recherche (LERS), 9 John Street, London WC1N 2ES1 The effects of fengabine were compared with those of amitriptyline in healthy elderly volunteers. Doses were administered double-blind and assessments were made before and after ingestion. 2 Psychomotor performance and cognitive ability were measured using tests of choice reaction time, tracking, critical flicker fusion threshold, memory scanning and word recognition. Subjective feelings were assessed using the Leeds sleep evaluation que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Objective awakening quality (attention, concentration, fine motor activity, reaction time performance) in normals showed -if measured at all -no decrements after SSRIs, as has been described with the classical sedative amitriptyline-type antidepressants [6,[9][10][11]. This is in line with the above-mentioned EEG findings exhibiting no deterioration in vigilance after SSRIs.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Objective awakening quality (attention, concentration, fine motor activity, reaction time performance) in normals showed -if measured at all -no decrements after SSRIs, as has been described with the classical sedative amitriptyline-type antidepressants [6,[9][10][11]. This is in line with the above-mentioned EEG findings exhibiting no deterioration in vigilance after SSRIs.…”
Section: Resultssupporting
confidence: 76%
“…Some classical antidepressant drugs such as the sedative ones of the amitriptyline type may improve sleep initiation and maintenance but often induce drowsiness during daytime, for which there is not only subjective but also some objective evidence [6,[9][10][11]. Nonsedative antidepressants such as the SSRIs generally do not exhibit this kind of side effect, but show inconsistent results concerning their effects on sleep quality (evaluated by subjective and objective means).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that use of amitriptyline may be limited by its effects on daytime functioning, in particular aspects of memory function that are disrupted even after long-term dosing (34). The study reported here suggests that there is limited evidence for cognitive function being compromised with amitriptyline treatment, and all three treatments were relatively well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…This test battery has been shown to be sensitive to an extensive range of psychotropic substances having very different mechanisms of activity. These include benzodiazepines (Hindmarch et al 1990), anaesthetics (Moss et al 1987) anti-dementia agents (Fairweather et al 1993a), hypnotics (Hindmarch et al 1990), neuroleptics (Hindmarch and Tiplady 1994), antidepressants (Ridout and Hindmarch 2001), antihistamines (Shamsi and Hindmarch 2000), cognitive enhancers (Rigney et al 1999), nicotine (Parkin et al 1998), alcohol (Ridout et al 2003a), and caffeine . While the precise mechanism of pregabalin's pharmacological activity at the neuronal level continues to be elucidated, the use of a validated and sensitive objective test battery assessing a wide range of cognitive and psychomotor skills, together with a selfrating scale (Line Analogue Rating Scales, LARS), allows the pharmacodynamic properties of pregabalin 450 mg/day to be determined.…”
Section: Introductionmentioning
confidence: 99%